Analisis Faktor – Faktor yang Mempengaruhi Risk Management Disclosure Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2015 – 2018 - Novian Aji Wijanarko; Rosita (CV. ALIM'SPUBLISHING, 2023)
This study aims to analyze and determine the effect of Leverage, Profitability, Company Size and Public Ownership on Risk Management Disclosure in manufacturing companies listed on the Indonesia Stock Exchange 2015 – 2018. This study focuses on all manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2018. 2018. Sample selection was done using purposive sampling method and obtained 23 samples with 92 data. The analytical method used in this research is Multiple Regression Analysis. Based on the result of the research, the variable leverage, profitability, firm size, and public ownership simultaneously affect risk management disclosure. Partially, the leverage variable, profitability variable and public ownership variable affect the risk management disclosure. While the variable size of the company does not affect the risk management disclosure.